(untitled) (World Bulletin of Social Sciences, 2023)
It is difficult to imagine the history of world art without Shakespeare. His influence on the development of theater art is incomparable. His tragedies are among the masterpieces of world literature.it will be discussed about the life and works of William Shakespeare